The Role of Family Education in Forming Islamic Character in Early Childhood (0-5 Years) at Talaga 1 Village, Talaga Raya District, Central Buton Regency - Nurfarahim, Wa Ode Adinda; Rusli, Rusli; Ridwan, Muhammad (Universitas Pahlawan Tuanku Tambusai, 2025)
The purpose of this study was to determine and examine how family education contributes to the formation of Islamic character in early childhood (ages 0-5 years) in Talaga 1 Village, Talaga Raya District, Central Buton Regency. To determine the influence of the family on the formation of children's character within the framework of Islamic faith, this study used qualitative methodology. The methods used to obtain data in qualitative descriptive research are documentation, interviews, and observations. Based on the results of the study, the family is the main educational factor that significantly influences and plays an active role in the formation of Islamic character through the instillation of moral values and good behavior. This study highlights the importance of the role of parents in instilling awareness and involvement in daily life education in children. In addition, this study can also provide knowledge about the role of the family as the main foundation for the formation of Islamic character in children. Thus, it is clear that parents have a very important role in efforts to form Islamic character in children.